Genetic merit of sires for ad libitum residual feed intake has no adverse effects on carcass and ham quality traits of restricted-fed heavy pigs - Chiara Mondin; Sara Faggion; Valentina Bonfatti; Luigi Gallo; Diana Giannuzzi; Stefano Schiavon; Paolo Carnier (PLoS ONE, 2026)
This study evaluated the influence of sire genetic merit for residual feed intake (RFI) on carcass and ham quality traits in heavy pigs raised under the restricted feeding conditions typical of Protected Designation of Origin dry-cured ham production. A total of 417 purebred C21 Goland pigs, offspring of 23 sires, were randomly assigned to ad libitum , restricted medium-protein, or restricted low-protein dietary treatments. Sire breeding values (EBV) for RFI were estimated using RFI records of ad libitum -fed progeny between 96 and 161 kg body weight. Sires were classified into three RFI groups: low EBV (LRFI), medium EBV (MRFI), and high EBV (HRFI). Effects of RFI sire groups were estimated on traits recorded on the restricted-fed progeny. Progeny of LRFI sires exhibited differences in carcass traits, including a significantly higher carcass weight gain (+0.03 kg/day, corresponding to +7.3%; p< 0.01) and increased green ham yield (+1.3%, p < 0.05), compared to those of HRFI sires. LRFI progeny showed no differences in ham fat depth, but exhibited improved subcutaneous fat quality, including higher saturation (increased stearic acid, reduced linoleic acid and polyunsaturated fatty acids) and lower iodine number, as well as firmer subcutaneous fat. No variation in ham weight loss during dry-curing was observed across RFI sire groups. These findings suggest that selection for improved RFI does not significantly compromise carcass and dry-cured ham quality in restricted-fed heavy pigs. Incorporating RFI into selection objectives for sire lines could therefore provide a viable strategy for balancing production efficiency and product quality in heavy pig systems. These findings apply to restricted-fed heavy pigs of the population studied, and potential genotype × feeding regime interactions may limit direct extrapolation to other genetic backgrounds or production systems.